2023
DOI: 10.1021/acs.chemmater.3c01607
|View full text |Cite
|
Sign up to set email alerts
|

Enlightening the Well-Controlled Photochemical Behavior of 1,1-Dicyanomethylene-3-Indanone-Functionalized π-Conjugated Molecules

Parag Das,
Cory T. Kornman,
Ion Ghiviriga
et al.

Abstract: Dicyanomethylene-3-indanone (INCN) is a popular electron acceptor showcased in hundreds of push−pull oligomers, including some of the best nonfullerene acceptor (NFA) materials used in small molecule-based bulk-heterojunction (BHJ) organic photovoltaics (OPVs). Consequences of the configuration (i.e., Z or E) and conformation (i.e., s-cis or s-trans) of the exocyclic olefin that conjugates INCN to π-conjugated molecules have largely been ignored. Two recent reports have implicated Z/E photoisomerization in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…Remarkably, no thermal isomerization was observed in either direction for 1- Z and 1- E in tetrachloroethane up to 80 °C (Figures S68–S69) or in acetonitrile- d 3 up to 60 °C (Figures S70–S71) over 120 and 80 h, respectively, which speaks to the bistable nature of the isomers. These findings deviate from our previous work on INCN-based donor–acceptor molecules, where we observed that higher polarity solvent induced faster thermal isomerization compared to a lower polarity solvent, in case of an INCN-monothiophene analog . In an H-bonding competitive solvent such as DMSO- d 6 at 60 °C, no Z → E thermal isomerization was observed within 80 h (Figure S72), but the 1- E isomer relaxes to 1- Z completely within 3 h (Figure S73).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Remarkably, no thermal isomerization was observed in either direction for 1- Z and 1- E in tetrachloroethane up to 80 °C (Figures S68–S69) or in acetonitrile- d 3 up to 60 °C (Figures S70–S71) over 120 and 80 h, respectively, which speaks to the bistable nature of the isomers. These findings deviate from our previous work on INCN-based donor–acceptor molecules, where we observed that higher polarity solvent induced faster thermal isomerization compared to a lower polarity solvent, in case of an INCN-monothiophene analog . In an H-bonding competitive solvent such as DMSO- d 6 at 60 °C, no Z → E thermal isomerization was observed within 80 h (Figure S72), but the 1- E isomer relaxes to 1- Z completely within 3 h (Figure S73).…”
Section: Resultscontrasting
confidence: 99%
“…These observations were repeatable even with the reaction vessels being covered with aluminum foil throughout the entire synthesis and purification processes to minimize the possibility of unintentional photoisomerization by ambient light. This unique isomer accessibility from synthesis is dissimilar to our previous work on RCN and INCN-functionalized thiophene oligomers, where only the more thermodynamically stable Z isomer could be obtained from synthesis.…”
Section: Resultsmentioning
confidence: 95%
“…Using the simplified 1,1-dicyanomethylene-3-indanon (INCN) compounds as model systems, Castellano et al conducted a series of designed experiments and complementary ground- and excited-state computations. 111 As shown in Fig. 9, they offer an exhaustive examination of the photochemical characteristics of a series of INCN-based molecules, featuring variations of INCN units in (hetero-)aryl substitution, alkyl group positioning, and halogen substitution.…”
Section: Chemical Stability and Degradation Mechanisms Of Electron Ac...mentioning
confidence: 99%
“…The rotation of vinyl groups in A–D–A type NFAs is the initial process that induced the photodegradation of NFAs, which is proved by the isolated photodegradation products in ITIC-NFAs. 37,80,111 Although the existence of out-side-chains in BTP-NFAs can suppress such rotation modes, the flexible vinyl groups are still able to rotate under illumination. As shown in Fig.…”
Section: Chemical Stability and Degradation Mechanisms Of Electron Ac...mentioning
confidence: 99%
See 1 more Smart Citation